PEMBERDAYAAN KELOMPOK KASPER WISATA BURAKE DI OBJEK WISATA BUNTU BURAKE, TORAJA - Tahirs, Jemi Pabisangan; Marina Palimbong, Stefani; Biringkanae, Astriwati (LPPM Universitas Bina Bangsa, 2024)
This activity is motivated by the role of Small and Medium Enterprises (UKM) as one of the drivers of the Indonesian economy to overcome unemployment and create employment opportunities. Empowering SMEs is very important to build an inclusive economy, where many parties play an active role in the wheels of the economy and can survive in the midst of global challenges. In addition, efforts are made to increase the capabilities, competitiveness and welfare of SMEs, so that they can contribute more optimally to the economy. The problems faced by SMEs are marketing difficulties, limited innovation and technology, especially limitations in preparing simple bookkeeping. In this activity, training will be provided for the Buntu Burake Tourism Kasper Group, Buntu Burake Village, Makale District, Tana Toraja Regency. Online marketing training regarding marketing strategies that utilize the internet and digital platforms to promote products or services to a wider audience. With business management and simple bookkeeping training, it contributes to business ethics and recording expenses, recording income, making cash books, making stock books, inventory books and profit and loss books.